Parasagittal hemispherotomy in hemispheric polymicrogyria with electrical status epilepticus during slow sleep: Indications, results and follow-up. (October 2019) - Fohlen, Martine; Dorfmüller, Georg; Ferrand-Sorbets, Sarah; Dorison, Nathalie; Chipaux, Mathilde; Taussig, Delphine
Highlights: Hemispherotomy is helpful in patients with drug-resistant epilepsy and hemispheric PMG. Hemispherotomy is indicated in patients with ESESS and unilateral PMG. Polymicrogyria-associated epilepsy is a rare and challenging surgical indication. Abstract: Purpose: Polymicrogyria (PMG), although the most common brain malformation, represents a low percentage among patients operated on for epilepsy. In cases of hemispheric PMG, electrical status epilepticus during slow sleep (ESESS) may occur leading to an aggravation of the neurological condition and a risk of drug resistance. In such cases, surgical treatment can be offered. Methods: From a population of 230 children who underwent hemispherotomy for epilepsy, we retrospectively reviewed the patients with unilateral PMG and drug-resistant ESESS focusing on clinical charts, electrophysiological data and post-surgical outcome. Results: Eighteen patients were operated on at a mean age of 7.2 years. The average age was 2 years at seizure onset and 4.4 years at diagnosis of ESESS. All the patients preoperatively had some degree of developmental delay associated with a hemiparesis. During ESESS all of them evidenced a cognitive decline and eight experienced a worsening of the hemiparesis; ESESS was resistant to at least three antiepileptic drugs. The outcome of epilepsy, with a mean follow-up of 12.8 years showed that ESESS disappeared in all patients while 16 of 18 became seizure-free. An improvement of behavior and cognitive condition was observed in all. Conclusion: Hemispherotomy can be helpful in patients with drug-resistant ESESS and hemispheric PMG while keeping in mind that more often an accurate medical treatment can be sufficient. The main benefit of surgery is to definitively stop the seizures and to withdraw the medical treatment while keeping in mind the risk of motor aggravation.